Dynamic Change of Volatile Fatty Acid Derivatives (VFADs) and Their Related Genes Analysis during Innovative Black Tea Processing - Zi-Wei Zhou; Qing-Yang Wu; Yang Wu; Ting-Ting Deng; Yu-Qing Li; Li-Qun Tang; Ji-Hang He; Yun Sun (Foods, 2024)
Volatile fatty acid derivatives (VFADs) play a significant role in contributing to flowery–fruity flavor black tea. Innovative black tea is typically crafted from aroma-intensive tea cultivars, such as Jinmudan, using defined production methodologies. In this study, the during-processing tea leaves of innovative black tea were applied as materials, and we selected a total of 45 VFADs, comprising 11 derived aldehydes, nine derived alcohols, and 25 derived esters. Furthermore, the dynamic variations of these VFADs were uncovered. Transcriptome analysis was performed to identify genes involved in the LOX (lipoxygenase) pathway, resulting in the identification of 17 CsLOX genes, one hydrogen peroxide lyase (CsHPL) gene, 11 alcohol dehydrogenases (CsADH) genes, 11 genes as acyl CoA oxidase (CsACOX) genes, and three allene oxide synthase (CsAOS) genes. Additionally, the expression levels of these genes were measured, indicating that the processing treatments of innovative black tea, particularly turn-over and fermentation, had a stimulation effect on most genes. Finally, qRT-PCR verification and correlation analysis were conducted to explain the relationship between VFADs and candidate genes. This study aims to provide a reference for illuminating the formation mechanisms of aroma compounds in innovative black tea, thereby inspiring the optimization of innovative processing techniques and enhancing the overall quality of black tea.